Mask Wearing Behavior to Prevent Acute Respiratory Tract Infections During the COVID-19 Pandemic Among Students in Jakarta - Apriana Rahmawati; Ulfa Nur Rohmah; Shenda Maulina Wulandari; Harizza Pertiwi (Babali Nursing Research, 2023)
Introduction: The incidence of acute respiratory infections (ARI) tends to be higher in urban areas, especially in Jakarta, the centre of activity in Indonesia. However, the COVID-19 pandemic forced people to wear masks in both urban and rural areas to prevent the virus from entering the respiratory tract. The purpose of this study was to identify the relationship between mask-wearing behaviour and outbreaks of acute respiratory infections during the COVID-19 pandemic among students in Jakarta. Methods: The design of this study was cross-sectional. The consecutive sampling technique was used to select 328 students as the respondents. The independent variable was mask-wearing behaviour (knowledge, attitude, practice). The dependent variable was ARI. The data were collected using a Google Forms questionnaire and then analysed by using the Chi-square test and multiple logistic regression test with a significance level of p < 0.05. Results: The result showed that respondents had good knowledge (57%), positive attitude (56.7%), good practice (50.6%), and did not have a history of ISPA (64.3%). The predictive factors affecting ARI showed significant results in the attitude domain (p <0.05; OR 1.907). Conclusion: This study found a connection between mask-wearing behaviour and knowledge, attitude, and practice to prevent ARI. We propose normalizing the use of masks even though the number of COVID-19 infections is gradually decreasing to prevent respiratory infections caused by the high rate of air pollution in urban areas.